1998
DOI: 10.1126/science.280.5372.2112
|View full text |Cite
|
Sign up to set email alerts
|

Direct Stimulation of the Guanine Nucleotide Exchange Activity of p115 RhoGEF by Gα 13

Abstract: Signaling pathways that link extracellular factors to activation of the monomeric guanosine triphosphatase (GTPase) Rho control cytoskeletal rearrangements and cell growth. Heterotrimeric guanine nucleotide-binding proteins (G proteins) participate in several of these pathways, although their mechanisms are unclear. The GTPase activities of two G protein alpha subunits, Galpha12 and Galpha13, are stimulated by the Rho guanine nucleotide exchange factor p115 RhoGEF. Activated Galpha13 bound tightly to p115 RhoG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
644
2
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 729 publications
(678 citation statements)
references
References 17 publications
29
644
2
1
Order By: Relevance
“…The ectopic expression of N19RhoA has been demonstrated to inhibit endogenous Rho function and the Ga13-RhoA pathway by forming non-productive complexes with guanine nucleotide exchange factors (GEFs) for Rho. 27 The ectopic expression of N19RhoA significantly reduced the percentage of fused CT26 cells whereas the expression of control acGFP1 vector had no effect (Figure 6f). …”
Section: Adam10 and Cd81 Regulate Localization Of Gtp-binding A13mentioning
confidence: 94%
“…The ectopic expression of N19RhoA has been demonstrated to inhibit endogenous Rho function and the Ga13-RhoA pathway by forming non-productive complexes with guanine nucleotide exchange factors (GEFs) for Rho. 27 The ectopic expression of N19RhoA significantly reduced the percentage of fused CT26 cells whereas the expression of control acGFP1 vector had no effect (Figure 6f). …”
Section: Adam10 and Cd81 Regulate Localization Of Gtp-binding A13mentioning
confidence: 94%
“…It was reported that P2Y 6 receptor coupled with Gα 12/13 signaling in cardiomyocytes [23] and human umbilical vein endothelial cells, phosphorylation of VASP was mediated by Gα 13 [19] and Rho activation was mediated by Gα 12/13 signals [34][35][36]. It has been established that Rho activation regulates cytoskeletal arrangements [37].…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 99%
“…There is a small subfamily of Dbl RhoGEFs whose members bind and serve as effectors for heterotrimeric G-protein a-subunits. This subfamily of RhoGEFs consists of Lsc/p115 RhoGEF (Glaven et al, 1996;Hart et al, 1996Hart et al, , 1998Whitehead et al, 1996;Kozasa et al, 1998), PDZ-RhoGEF (Rholike GEF containing a PDZ (PSD-95/Disc-large/ZO-1) domain/GTRAP-48 (Fukuhara et al, 1999), and leukemia-associated RhoGEF (LARG) (Fukuhara et al, 2000;Reuther et al, 2001). These RhoGEFs can bind Ga 12/13 through a regulator of G-protein signaling (RGS)-like domain in their N-terminus.…”
Section: Introductionmentioning
confidence: 99%